2021
DOI: 10.1371/journal.pone.0251495
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stimulation of group II metabotropic glutamate receptors in the medulla oblongata attenuates hypertension development in spontaneously hypertensive rats

Abstract: Baroreflex dysfunction is partly implicated in hypertension and one responsible region is the dorsal medulla oblongata including the nucleus tractus solitarius (NTS). NTS neurons receive and project glutamatergic inputs to subsequently regulate blood pressure, while G-protein-coupled metabotropic glutamate receptors (mGluRs) play a modulatory role for glutamatergic transmission in baroreflex pathways. Stimulating group II mGluR subtype 2 and 3 (mGluR2/3) in the brainstem can decrease blood pressure and sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Thus, we initially suspected that mGluR2/3 antagonists could have a therapeutic potential for hypertension treatment. Although this idea was negated, our results were consistent with our previous study, which showed mGluR2/3 “agonists” could suppress hypertension development in young SHRs [ 22 ]. Thus, mGluR2/3 could be important for hypertension development in SHRs and these receptors, and/or neurons expressing these receptors, may have memory functions in blood pressure regulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we initially suspected that mGluR2/3 antagonists could have a therapeutic potential for hypertension treatment. Although this idea was negated, our results were consistent with our previous study, which showed mGluR2/3 “agonists” could suppress hypertension development in young SHRs [ 22 ]. Thus, mGluR2/3 could be important for hypertension development in SHRs and these receptors, and/or neurons expressing these receptors, may have memory functions in blood pressure regulation.…”
Section: Discussionsupporting
confidence: 92%
“…For mGluRs intervention, we chronically applied a selective mGluR2/3 antagonist, LY341495, into the dorsal medulla oblongata with the aid of an osmotic pump to block endogenous glutamate in rats during 6–12 weeks of age. In our previous study, we found that mGluR2/3 agonist treatment into the dorsal medulla oblongata could suppress the development of hypertension [ 22 ]. However, as NTS microinjection of the mGluR2/3 antagonist could also decrease mean blood pressure by approximately 18 mmHg in normotensive rats [ 18 ], the current study was considered very important for understanding pathophysiological mechanisms of blood pressure regulation.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work showed that uridine has a hypoglycemic effect that protects against diabetes-mediated functional and structural damage to cardiac mitochondria and disruption of mitochondrial quality-control systems in the diabetic heart [ 48 ]. metabotropic glutamate receptors —Chronic stimulation of group II metabotropic glutamate receptors in the medulla oblongata attenuates hypertension development in spontaneously hypertensive rats [ 49 ]. Group III metabotropic glutamate receptors regulate hypothalamic pre-sympathetic neurons through opposing presynaptic and postsynaptic actions in hypertension [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…metabotropic glutamate receptors —Chronic stimulation of group II metabotropic glutamate receptors in the medulla oblongata attenuates hypertension development in spontaneously hypertensive rats [ 49 ]. Group III metabotropic glutamate receptors regulate hypothalamic pre-sympathetic neurons through opposing presynaptic and postsynaptic actions in hypertension [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mGluR2/3 are also involved in the functional connection between NTS neurons and parasympathetic preganglionic neurons of the DMV, as well as to other areas, and modulate vagal sensory input and gastric motor responses [96]. For example, blocking mGluR2 signaling in the dorsal brainstem, an area including NTS (which is involved in baroreflex pathways through glutamatergic transmission), has been shown to lead to higher blood pressure in animal research [97], while mGluR2/3 stimulation in the same area can decrease blood pressure and sympathetic nervous activity [98]. Our findings, thus, suggest favorable effects of mGluR2/3 agonism on stress-related autonomic responses in accordance with animal data [95,99] and are relevant to individual stress responsiveness and anxiety and stress-related disorders susceptibility.…”
Section: Glutamatergic Signaling Stress and Ans Reactivitymentioning
confidence: 99%